2022
DOI: 10.21203/rs.3.rs-2095779/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shorter Planning Depth and Higher Response Noise During Sequential Decision-Making in Old Age

Abstract: Forward planning is crucial to maximize outcome in complex sequential decision-making scenarios. In this cross-sectional study, we were particularly interested in age-related differences of forward planning. We presumed that especially older individuals would show a shorter planning depth to keep the costs of modelbased decision-making within limits. To test this hypothesis, we developed a sequential decision-making task to assess forward planning in younger (age < 40 years; n = 25) and older (age > 60 y… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…For distributions of PD across groups and step condition see Figure 3. Consistent with previous findings (Steffen et al, 2022), we observed neither a significant effect of the noise condition ( t (182)=-1.253, p =.21) nor a significant interaction effect of group x noise ( t (182)=1.086, p =.28).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…For distributions of PD across groups and step condition see Figure 3. Consistent with previous findings (Steffen et al, 2022), we observed neither a significant effect of the noise condition ( t (182)=-1.253, p =.21) nor a significant interaction effect of group x noise ( t (182)=1.086, p =.28).…”
Section: Resultssupporting
confidence: 88%
“…Participants entered their responses via keyboard with key ‘S’ indicating the jump action and the right arrow key indicating the move action. For an exhaustive description of the SAT see Steffen et al (2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations